2004
DOI: 10.1152/ajpheart.00967.2001
|View full text |Cite
|
Sign up to set email alerts
|

Acute and specific collagen type I degradation increases diastolic and developed tension in perfused rat papillary muscle

Abstract: Collagen degradation is suggested to be responsible for long-term contractile dysfunction in different cardiomyopathies, but the effects of acute and specific collagen type I removal (main type in the heart muscle) on tension have not been studied. We determined the diastolic and developed tension length relations in isometric contracting perfused rat papillary muscles (perfusion pressure 60 cmH(2)O) before and after acute and specific removal of small collagen struts with the use of purified collagenase type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…This decrease in collagen in the papillary muscles was accompanied by a marked decrease in systolic function (i.e., reduced amount and rate of shortening, reflected by developed tension (T) and +dT/dt) without affecting isolated cardiomyocyte contractility, leading the authors to conclude that myocardial fibrillar collagen is a major contributor to normal myocardial systolic performance. In contrast to these findings, Lamberts et al [58] reported myocardial function was improved following specific degradation of collagen type I (i.e., an increase in developed tension and the rate of relaxation). Unfortunately, relaxation rates were not reported in the Baicu study, precluding comparison of this parameter.…”
Section: Alterations In Ecm Fibrillar Collagen and Left Ventricular Smentioning
confidence: 83%
“…This decrease in collagen in the papillary muscles was accompanied by a marked decrease in systolic function (i.e., reduced amount and rate of shortening, reflected by developed tension (T) and +dT/dt) without affecting isolated cardiomyocyte contractility, leading the authors to conclude that myocardial fibrillar collagen is a major contributor to normal myocardial systolic performance. In contrast to these findings, Lamberts et al [58] reported myocardial function was improved following specific degradation of collagen type I (i.e., an increase in developed tension and the rate of relaxation). Unfortunately, relaxation rates were not reported in the Baicu study, precluding comparison of this parameter.…”
Section: Alterations In Ecm Fibrillar Collagen and Left Ventricular Smentioning
confidence: 83%
“…Rueckschloss et al [23] have reported that soluble FN enhanced Ca 2+ current in cardiomyocytes while soluble RGD peptide did not have any effect on Ca 2+ current. Lamberts et al used a specific type 1 collagenase enzyme and observed an increase in diastolic and developed tension [61]. Laminin binding to β1 integrins modulates Ca L through signaling pathways linked to adrenergic and cholinergic receptors signaling in cat atrial myocytes [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…85 Digestion of purely endomysial fibers has the opposite effect. 86,87 Recent studies have begun targeting signaling factors to fibrosis, including transforming growth factor-␤, 88 the sodium-hydrogen exchanger, 89 angiotensin II receptor-mediated signaling, 90 and chymase, 91 correlating changes in collagen/fibrosis to chamber stiffening. Other studies have degraded collagen in normal and pressureload hypertrophied papillary muscles with plasmin 92 or oxidized glutathione and hydroxyproline, 93 and inhibited collagen cross-links with ␤-aminopropionitrile.…”
Section: What Is the Impact Of Altered Collagen/fibrosis?mentioning
confidence: 99%